Analisis Sistem Integrasi Padi Gogo Dengan Usaha Sapi Potong di Lahan Tadah Hujan - Teguh Prasetyo; Cahyati Setiani (Jurnal Riset Agribisnis dan Peternakan, 2020)
Most of the farmers in rainfed land are integrated upland rice farming with beef cattle farming. Farmers try to make an approach through the agricultural concept of integrating crops and livestock, namely optimizing the resources they have such as land, labor, skills, and local culture, so that external input can be minimized. The concept of an integrated crop and livestock farming system is based on the concept of sustainable agriculture, which puts forward efforts to increase yields that can be sustainable, both in terms of plants and livestock. This means continuously high productivity of crops and livestock and at the same time maintaining the resource base. Both of them synergize with each other and supply mutual input, so that input from outside can be reduced. To determine the system of integration of upland rice and beef cattle, an assessment of the application of upland rice farming technology packages that are integrated with beef cattle business in rainfed land has been carried out. The purpose of this study was to determine the production cycle of upland rice and beef cattle farming as well as the productivity and financial value of the beef cattle business. The assessment method uses a field trial method. The productivity of upland rice in the study locations ranged from 5.33 to 6.38 tonnes/ha of milled dry unhulled (GKP) harvested or 4.82 - 5.31 tonnes/ha of milled dry unhulled (GKG). Apart from yields in the form of rice, upland rice farming can also produce rice straw between 6.65 - 9.27 tonnes/ha. The productivity of breeding cows in the research location is still low, due to factors of feeding and mating management. The highest cost in a beef cattle business for reproductive purposes is the purchase of prospective broodstock or seedlings, namely 79.66% of the total cost, for feed costs (grass and straw), and labor, respectively 13.86%, 1.78%, while still costs 4.55% of the total costs. From the results of the ratio analysis between revenue to expenditure, it is obtained that an R / C ratio of 1.12 means that every capital investment for beef cattle is IDR 10,000,000 will get IDR 11,200,000 / 6 months. Manure fermentation can increase the ratio of C / N and C Organic so that it can approach the Quality Standard of the Ministry of Agriculture No: 70 / SR.140 / 10/2011. The straw fermentation that is carried out can increase digestibility and protein content, but in its provision, it must be added with concentrate, so that the feed given is in accordance with the needs of the cows.